2012
DOI: 10.1007/s10508-012-9930-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Infidelity in China: Prevalence and Gender-Specific Correlates

Abstract: The nature of extra-relational sex in societies with rapidly changing sexual mores and widespread commercial sex remains under-explored. The 2006 Sexuality Survey of China provides a national probability survey with data on 3,567 people 18-49 years old who were in a marital (89%) or dating/cohabiting (11%) relationship. In attitudes, extramarital sex was completely unacceptable to 74% of women and 60% of men and either somewhat or completely unacceptable to 95% of women and men. Most (77%) women wanted severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 55 publications
3
36
0
1
Order By: Relevance
“…Although attitudes toward pre-marital sex were somewhat less traditional, as many as 71% of Chinese people disapproved of premarital sex. The clear evidence of considerable internal variation in sex ideologies across China also calls into question the generalization that a national "sexual liberation" is under way in China, which is largely based on behavioral observations (Parish et al, 2007;Zhang et al, 2012). Nevertheless, the importance of studying sex ideologies does not lie in the accuracy with which we can infer behavior from ideology.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although attitudes toward pre-marital sex were somewhat less traditional, as many as 71% of Chinese people disapproved of premarital sex. The clear evidence of considerable internal variation in sex ideologies across China also calls into question the generalization that a national "sexual liberation" is under way in China, which is largely based on behavioral observations (Parish et al, 2007;Zhang et al, 2012). Nevertheless, the importance of studying sex ideologies does not lie in the accuracy with which we can infer behavior from ideology.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Indeed, according to a report on sexual health in China, the proportion of Chinese who have had premarital sex increased from 15% in 198915% in to 40% in 199415% in and 71% in 201215% in (Ruan, 2013. Analyzing data from China's 2006 Sexuality Survey, Zhang, Parish, Huang, and Pan (2012) reported that 4.5% of women and 16.5% of men have had extramarital sex. Estimates indicate that approximately 3% to 5% of the Chinese population are homosexual, and that around 11% of unmarried men and 5.8% of married men have had sex with another man (Neilands, Steward, & Choi, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that infi delity can have negative effects on the relationship, and may be the most feared and devastating experience of a marriage (Pittman, 1994), which may lead to divorce (Zordan & Strey, 2011). A systematic review of the literature (Scheeren, 2016) suggested a prevalence of infi delity between 1.2% (Beaulieu-Pelletier, Philippe, Lecours, & Couture, 2011) and 89.4% (Zhang, Parish, Huang, & Pan, 2012). In Brazil, the study conducted by Goldenberg (2011), with 1,279 men and women from the urban middle class of Rio de Janeiro, showed that 60% of the men and 47% of the women had been unfaithful.…”
Section: Infi Delidad Conyugal: La Experiencia De Hombres Y Mujeres Rmentioning
confidence: 99%
“…It is estimated to be 25.0% of monogamous relationship in United States [52] and 15.2% of Chinese migrant workers [53]. Generally, the frequency is higher in men than women in both the western [54] and eastern countries [55]. If so, our results may be challenged invalid as HSA patients may selectively report committing intercourse only with spouses or usual partners but not extradyadic ones to protect their dyadic relationship.…”
Section: Discussionmentioning
confidence: 75%